Directing reaction pathways via in situ control of active site geometries in PdAu single-atom alloy catalysts - Mengyao Ouyang; Konstantinos G. Papanikolaou; Alexey Boubnov; Adam S. Hoffman; Georgios Giannakakis; Simon R. Bare; Michail Stamatakis; Maria Flytzani-Stephanopoulos; E. Charles H. Sykes (Nature Communications, 2021)
Single-atom alloys are promising catalysts for a number of different reactions. Here, the authors demonstrate that carbon monoxide can be used to transition a PdAu catalyst between a single atom and a cluster phase which exhibit distinct selectivities for ethanol dehydrogenation.